HAK ASASI MANUSIA (HAM) DI INDONESIA DILIHAT DALAM PERSPEKTIF ISLAM - Suhaimi Hamid (Universitas Batanghari Jambi, 2014)
“Human rights could generally be defined as those rights which are inherent in our nature and without which we cannot live as human biengs”Understanding as mentioned above, it is a human rights as something that became a standard of achievement for all people and nations of the world Milestones of Human Rights begins with the initiation of the Magna Carta in England in 1252 and more significantly after the initiation of the Universal Declaration of Human Rights (UDHR 1948 )Therefore, as an independent country and dignity , the rights incorporated into the formulation of Pancasila and the 1945 Constitution , and after the inclusion of human rights into the 1945 material certainly a consequence that human rights is a constitutional right guaranteed by law in Indonesia . Human Rights initiated by the western world and has been incorporated into the 1945 Constitution there are certainly differences with the Islamic concept of human rights ; among others, Human Rights in Islam Tawheed and Aqeedah born of appreciation by Allah to perfect Insan over creation. Besides, it also looked at the man in Islam similarity in accordance with his nature .keyword : Human Rights in Indonesia seen in Islamic Perspective.